The Influence of Trust, Customer Value and Customer Relationship Management (CRM) on Loyalty Through Customer Satisfaction of Republic of Indonesia Employee Cooperatives University of Jember - Anton Yuliansyah; Rozy Khadafi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study seeks to analyze the influence of Trust Variables, customer value, and Customer Relationship Management (CRM) on customer satisfaction within the Republic of Indonesia Civil Servants Cooperative at the University of Jember. Primary data is employed for the research, and the path analysis method is applied using the SPSS 21 analysis tool. The findings highlight that Trust, customer value, and CRM factors exert both direct and indirect effects on customer satisfaction